PENGARUH FASILITAS BELAJAR DAN KOMUNIKASI KELUARGA TERHADAP MOTIVASI BELAJAR SISWA TINGKAT MENENGAH ATAS DAN KEJURUAN SE - KECAMATAN BUNTU PEPASAN - Johanis Martoguhun; Mesta Limbong; Hotmaulina Sihotang (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2022)
The purpose of this study was to determine how much influence learning facilities and family communication have on the learning motivation of upper secondary level students in Buntu Pepasan District. In this study the approach used was a quantitative approach. The sampling technique used purposive sampling technique. The number of samples was 62 people. Data collection techniques were carried out by distributing questionnaires directly to the research site. Instrument testing and data analysis were carried out with the help of SPSS Version 25. In testing the hypothesis, a partial test was carried out with the